What Is the International Best Practice for Regulation of Financial Markets? From A Legal and Practical Perspective - Al-Shebli, Abdullah; Alhajri, Thafar M (Journal of Ecohumanism, 2024)
Financial markets have become increasingly intricate as a result of technical advancements, the introduction of new financial instruments, and the process of globalization. This necessitates the regulation of financial markets. Individual investors are vulnerable to exploitation in the absence of market regulation. This article aims to address the question of how financial markets should be regulated.This article seeks to emphasize the growing need for regulation in financial markets. It will explain the many regulation models used to regulate financial markets. It deals with the conflict of interest that arises between the financial gains of the capital markets and the obligation to oversee and enforce regulations to maintain fairness. This article will use a descriptive and analytical legal research methodology.Economists are prolific at formulating theories on various subjects, including markets and their regulation. However, the need for regulation is clear due to the numerous financial crises and scandals, from which Kuwait is not immune. Regardless of the theories, the reality is that financial crises have occurred, and people have suffered as a result, which could have been avoided by having sound regulations in place. There is an increasing trend toward intervention in and regulation of the markets.